The Role of Health Education by Community Nurses in Reducing Smoking Habits in Adolescents - Mustar; Sri Hartati; Herlina Lidiyawati (PT. Anagata Sembagi Education, 2024)
This study explores the role of health education by community nurses in reducing smoking habits among adolescents through qualitative interview methods. The background of this problem is rooted in the long-term health impact of smoking habits, which are often influenced by factors such as peer influence and advertising, as well as a lack of knowledge about the dangers of smoking. The purpose of this study is to understand how health education can affect changes in adolescents' smoking knowledge, attitudes, and behaviors, as well as to assess the role of social support from the family. The method used was in-depth interviews with 20 adolescents who had participated in a health education program guided by a community nurse. The interview data was analyzed using thematic analysis techniques to identify key patterns and themes. The results showed that health education significantly increased adolescents' knowledge about the dangers of smoking and improved their attitudes towards the habit. Teens also reported gaining practical skills to resist the offer of smoking, and family support played an important role in their success in quitting smoking. The implications of this study emphasize the importance of integrating health education with family support to increase program effectiveness. Health education programs by community nurses must be continued and expanded, involving other elements of society, and adapted to the needs of adolescents and technological developments. Support from various parties, including government policies and health agencies, is critical to strengthening these programs and creating an environment that supports the overall health of adolescents Keywords : Health Education, Community Nurses, Smoking, Adolescents